(untitled) (Revista Contexto & Educação, 2026)
In the light of contemporary youth, this article aims to understand how the constitution of the “I” takes place. In view of the objective, it is asked: how does the globalized world and its products, whether physical or virtual, influence the constitution of young people’s identity? To answer the question, a qualitative approach research was carried out with the participation of 20 young people, all students, among which: 10 are from public schools and 10 from private schools, all aged between 15 and 17 years, from a city located in the extreme west of Santa Catarina. The way to come to understand the aforementioned question and that gives meaning to the research, had open and closed questions on the subject. In addition, another method chosen was that of a focus group, in which, during five meetings, conversations took place about the media, social networks, relationships, the influence that social networks have on students and how much it influences them in the constitution of identities. In this sense, it can be concluded that the current moment in which young people live is an existential period different from that of past generations, when the concern with self-recognition and making oneself recognized was much more noticeable.